Attending to what’s important: what heat maps may reveal about attention, inhibitory control, and fraction arithmetic performance - Godwin, Karrie E.; Thompson, Clarissa A.; Kaur, Freya; Iwai, Yuika; Fitzsimmons, Charles J.; Taber, Jennifer M. (Frontiers in Psychology, 2023)
Math proficiency is an important predictor of educational attainment and life success. However, developing mathematical competency is challenging, and some content (e.g., fractions) can be enigmatic. Numerous factors are suspected to influence math performance, including strategy knowledge, attention, and executive functions. In two online studies, we investigated the relationship between adults’ fraction arithmetic performance, confidence judgments, inhibitory control (a component of executive functions), and attention to strategy-relevant fraction components. We explored the utility of heat maps (based on mouse clicks) to measure adults’ attention to strategy-relevant fraction arithmetic components (operationalized according to each mathematical operation). In Study 1, attending to strategy-relevant fraction components was correlated with inhibitory control, but this finding did not replicate in Study 2. Across both studies, inhibitory control and attention to strategy-relevant fraction components were correlated with arithmetic accuracy. Intraindividual variability in participants’ attention to strategy-relevant fraction components was also found. Our findings suggest that heat map questions may be a viable alternative to assess participants’ attention during fraction tasks and that attention to specific fraction-arithmetic problem features is related to problem-solving accuracy.